Analisa Kualitas Selai dengan Penggunaan Sari Buah Sijentik (Bacceura Polyneura) (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Fruit jam is a type of preserved food made mainly from fruit, aimed at extending shelf life. It consists of 45% fruit juice and 55% sugar, with a total soluble solid content of at least 65%. Sijentik (Baccaurea polyneura) is an exotic tropical fruit from Lima Puluh Kota region in West Sumatra, which is not well-known and is underutilized by the local community. This research aims to maximize the utilization of this fruit to enhance its economic value and add variety to the types of jam available in the market. The study analyzes the effect of using sijentik fruit juice on the quality of fruit jam (color, aroma, texture, and taste) using a pure experimental method by conducting three (3) trials with four (4) different treatments. The data type is primary data sourced from 30 semi-trained panelists who filled out the organoleptic test format. The technique used is analysis of variance (ANOVA) to analyze the organoleptic test data. The results of this study indicate that there is a significant effect in several categories of sensory tests from the use of sijentik fruit juice on the quality of the jam. There is a significant effect in several categories of sensory tests, namely color, texture, and taste. However, there is no significant effect for aroma.